The “Unhappy Consciousness”. A Paradigm of Reason’s Speculative Power - Scaglia, Lara (ETHICS IN PROGRESS, 2022)
One way to address the question concerning the nature of reason consists in inquiring rational anxieties such as the tension between changeable and unchangeable. The yearning of the particular towards the universal, the iterative, interminable quest of the thinking is namely something which seems to be proper of many systems of classical German philosophy (but not only). In this paper I want to consider this problematic focusing on the figure of the unhappy consciousness which is perhaps the clearest expression of this tension and use it to approach Hegel’s account on speculative reason. After recalling – in the first section – the figures which precede the unhappy consciousness, I will address the question concerning the historicity and universality of the development of the consciousness, asking if it is the case that the unhappy consciousness belongs only to a particular historical age (and needs specific historical preconditions) or if it expresses a general feature of reason or of human experience. In the second and the third sections, namely, I will try to defend this second interpretation by showing that the unhappy consciousness not only is central in Hegel’s system and is re-echoed in several figures of the Phenomenology of the Spirit but it is also central in other philosophical systems. For instance, as I will show in the fourth section, Kant’s ethical thinking could be read under the light of the unhappy consciousness, whose unsatisfied yearning towards the universal is the expression and source of the speculative or metaphysical thinking.